2013
DOI: 10.5194/acp-13-11595-2013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and hygroscopic properties of aerosol particles over the Aegean Sea

Abstract: Abstract. The chemical composition and water uptake characteristics of sub-micrometre atmospheric particles over the region of the Aegean Sea were measured between 25 August and 11 September 2011 within the framework of the Aegean-Game campaign. High temporal-resolution measurements of the chemical composition of the particles were conducted using an airborne compact time-of-flight aerosol mass spectrometer (cToF-AMS). These measurements were performed during two flights from the island of Crete to the island … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Airborne measurements performed above the Aegean Sea during the Aegean-Game (Aegean Pollution: Gaseous and Aerosol airborne MEasurements) campaign (Bezantakos et al, 2013), which was coupled with ACEMED, showed similar values for κ. Over multiple years, measurements of particle hygroscopicity at the South Aegean site of Finokalia, Crete, also exhibit very similar values (Bougiatioti et al, 2009(Bougiatioti et al, , 2011Kalkavouras et al, 2016).…”
Section: Hygroscopic Growth Modelmentioning
confidence: 79%
See 1 more Smart Citation
“…Airborne measurements performed above the Aegean Sea during the Aegean-Game (Aegean Pollution: Gaseous and Aerosol airborne MEasurements) campaign (Bezantakos et al, 2013), which was coupled with ACEMED, showed similar values for κ. Over multiple years, measurements of particle hygroscopicity at the South Aegean site of Finokalia, Crete, also exhibit very similar values (Bougiatioti et al, 2009(Bougiatioti et al, , 2011Kalkavouras et al, 2016).…”
Section: Hygroscopic Growth Modelmentioning
confidence: 79%
“…Given that the hygroscopic growth data reported by Bezantakos et al (2013) correspond to RH > 80 %, this consistency between predictions and observations is a strong indication that the internal mixture assumption applies and that the AMS composition data are representative of the ambient aerosol. Moreover, the drop in predicted hygroscopicity for RH < 80 % is consistent with observed behavior for aerosol particles (e.g., Guo et al, 2015).…”
Section: Hygroscopic Growth Modelmentioning
confidence: 90%
“…In particular, the systematic measurements of aerosols in the southern AS region (Finokalia) during late summer have shown that 30-35 % of OA comes from biomass burning in the eastern Balkans and at the European countries surrounding the Black Sea. Bossioli et al (2014) have shown that the wildfire emissions sector contributes on average ca. 50-60 % to the total PM 1 OA mass predictions in the AS region during the summer, which further supports our speculation.…”
Section: E Athanasopoulou Et Al: Aerosol Chemistry Above An Extendementioning
confidence: 99%
“…For the cases analysed herein, we consider a κ value of 0.4 to be characteristic for particles in the south-eastern Aegean Sea (Bezantakos et al, 2013). A more detailed comparison of dry in situ measurements with ambient remote sensing retrievals is outside the scope of this analysis, but it is very important when combining these different techniques (e.g.…”
Section: Surface In Situmentioning
confidence: 99%